Analisis Kebutuhan E-Book Interaktif berbasis Kearifan Lokal dalam Pembelajaran Teks Eksposisi - Bima Mhd Ghaluh; Afnita Afnita; Ella Wulandari (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
The lack of use of e-books in teaching expository texts at high school level is the background of this research which aims to analyze the demand for e-books based on local wisdom. The method used is descriptive and qualitative with the subject of research being high school principals and teachers in Padang City. The data collection tools used are interview guidelines and documentation. Data analysis uses Miles & Huberman data analysis with data reduction, data presentation, and data validation. The results of the research show that e-books in schools do not meet the requirements for implementation in learning. Therefore, schools need e-books that are suitable for the curriculum and based on local wisdom and HOTS. This research is expected to be a reference in the creation or development of e-books as media for teaching expository texts at high school level. Keywords: e-book, interactive, local wisdom, expository text.